Experimental Characterization and Seasonal Energy Potential Assessment of Municipal Solid Waste in Kano City, Nigeria - Sirajo ALHASSAN; Abdullahi A. ADAMU; Mohammed T. JIMOH (FUDMA Journal of Engineering and Technology, 2026)
Municipal solid waste (MSW) management remains a critical environmental challenge in rapidly urbanizing regions such as Kano City, Nigeria. This study presents an experimental characterization and energy potential assessment of MSW based on seasonal variation (dry and wet seasons). Representative samples were collected from four major dumping sites: Sallari, Maimalari, Uba Gama, and Hajj Camp. Proximate and ultimate analyses were conducted to determine moisture content, ash content, volatile matter, fixed carbon, and elemental composition (C, H, O, N, and S). The results reveal clear seasonal differences in MSW properties. Moisture content ranged from ≈28.25% in the dry season to ≈44.25% in the wet season, while ash content varied between ≈28.50% and ≈31.50%. Volatile matter increased from ≈19.75% in the wet season to ≈28.40% in the dry season, and fixed carbon ranged from ≈4.50% to ≈14.85%. Ultimate analysis revealed relatively stable elemental composition across seasons, with carbon (≈45.57–46.23%), hydrogen (≈6.49–6.58%), oxygen (≈45.31–46.31%), nitrogen (≈1.42–1.43%), and sulfur (≈0.23–0.24%). These results indicate moderate fuel characteristics with variability influenced by seasonal conditions. The higher heating value (HHV) was estimated to range between ≈16.43 and ≈16.95 MJ/kg, while the lower heating value (LHV) ranged from ≈13.92 to ≈14.82 MJ/kg, with higher values observed during the dry season due to reduced moisture content. The findings suggest that although high moisture and ash contents may limit the efficiency of direct combustion, the waste stream possesses moderate energy recovery potential. Overall, the findings confirm the suitability of MSW in Kano City for thermochemical conversion technologies such as pyrolysis and gasification, particularly with appropriate pre-treatment strategies. This study provides robust, seasonally resolved experimental data for supporting sustainable waste-to-energy planning and decision-making in rapidly growing urban environments.